1 answer:
Answer:
c² - 14cd + 49d²
Step-by-step explanation:
Given
(c - 7d)²
= (c - 7d)(c - 7d)
Each term in the second factor is multiplied by each term in the first factor, that is
c(c - 7d) - 7d(c - 7d) ← distribute both parenthesis
= c² - 7cd - 7cd + 49d² ← collect like terms
= c² - 14cd + 49d²
You might be interested in
Answer:
280
Step-by-step explanation:
D = kt
105 = 3k
k = 35
D = 35t
D = 35(8) = 280
0.75 is 3/4 or 6/8, which is less than 7/8
Answer: x = 1 + 0.5c
Step-by-step explanation:
Answer:
x = -4
Step-by-step explanation:
x = 3 - 7
x = - (7 - 3)
x = -4
M=0-5/1-0
m=-5/1=-5
y-y1=m*(x-x1)
y-5=-5(x-0)
y-5=-5x
y=-5x+5